Working with teaching assistants and other support staff for inclusive education - Chambers, Dianne (International perspectives on inclusive education ;, 2015)
Support staff in schools are increasingly recognised as playing an important, though often undefined, role in inclusive education. While there has been some research on how best to work with support staff, this book provides readers with a comprehensive examination of roles and responsibilities within the classroom. Issues in determining appropriate ways to work effectively with support staff are raised, along with strategies teachers can use to enhance the collaborative and reflective nature of working with others.